The classification of urban growth pattern using topological relation border length algorithm: An experimental study - Ghani N.L.A.; Abidin S.Z.Z. (Springer Science and Business Media Deutschland GmbH, 2023)
Expansion; Infill drilling; Topology; Boundary analysis; Classification results; Classification rules; Topological relations; Urban growth patterns; Urban regions; Urban growth